2001
DOI: 10.1046/j.1537-2995.2001.41030317.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial oftransfusion‐related acute lung injury: is plasma from multiparous blood donors dangerous?

Abstract: Plasma from multiparous blood donors may impair pulmonary function in intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 39 publications
(49 reference statements)
8
119
1
5
Order By: Relevance
“…Other supportive clinical data include a prospective randomized crossover study of two units of plasma from multiparous donors (≥ 3 live births) versus control plasma in 105 intensive care patients. 26 This study found that patients who received study plasma had impaired lung function as evidenced by a decrease in PaO 2 :FiO 2 ratio versus controls. Dykes et al 27 reported TRALI in a single lung transplant recipient after a red cell transfusion containing HLA-B44 antibodies.…”
Section: Immune (Antibody)-mediated Tralimentioning
confidence: 74%
“…Other supportive clinical data include a prospective randomized crossover study of two units of plasma from multiparous donors (≥ 3 live births) versus control plasma in 105 intensive care patients. 26 This study found that patients who received study plasma had impaired lung function as evidenced by a decrease in PaO 2 :FiO 2 ratio versus controls. Dykes et al 27 reported TRALI in a single lung transplant recipient after a red cell transfusion containing HLA-B44 antibodies.…”
Section: Immune (Antibody)-mediated Tralimentioning
confidence: 74%
“…The clinical significance of plasma from multiparous donors was confirmed by Palfi et al (2001). They showed that, in a prospective randomised controlled trial of 100 intensive care patients receiving a unit of control plasma and, 4-h later, a plasma unit from a multiparous donor or vice versa, transfusion of plasma from multiparous donors was associated with significantly lower oxygen saturation and higher TNF-a concentrations than transfusion of control plasma.…”
Section: Prevention Of Tralimentioning
confidence: 94%
“…This antibody-antigen interaction then initiates a cascade of cellular activity in the lung, resulting in endothelial damage and capillary leakage into alveoli [45]. Women who have had multiple pregnancies and patients with a history of prior transfusions are the most likely donors to be implicated in cases of TRALI [46]. Of particular interest in the obstetric setting is the association of TRALI in children whose mothers act as directed blood donors.…”
Section: Transfusion-associated Acute Lung Injurymentioning
confidence: 99%